An Analysis of Factors Influencing Students’ Speaking Skill in Triatma Mulya University - Kurniawati, Kadek Lina (English Education Department STKIP Agama Hindu Singaraja, 2024)
As a productive skill, speaking plays an important role as a means of effective communication. In English learning process, speaking is considered of the most difficult aspects due to many students are hard to express themselves in English. The population in this study is all of the students in the English Language Education at Triatma Mulya University. This study aims at knowing the factors affecting students’ English speaking skill. This review paper focusses on the research in term of speaking, especially some factors affecting students’ speaking skill. Based on the review of literature and the result of interview showed that the students’ psychological and students’ linguistic problems become the factors affecting students’ English speaking skill. The students’ psychological problem includes lack of confidence (posture, gesture, and eye contact) and fear/anxiey. However, the students’ linguistics problem includes vocabulary, grammar, and pronunciation. This study can be used by the teachers and future researchers who focused on factors affecting students’ English speaking skill.